The molecular chaperone hsp40 regulates the activity of P58(IPK), the cellular inhibitor of PKR - Melville, Mark W. (The National Academy of Sciences of the USA, 1997)
The interferon-induced double-stranded RNA-activated protein kinase, PKR, likely contributes to both the antiviral and the antiproliferative effects of interferon. We previously found that influenza virus avoids the translational inhibitory effects of activated PKR by activating a cellular inhibitory protein, termed P58(IPK), based on its M(r) of 58,000. P58(IPK) is a member of the tetratricopeptide family of proteins and possesses significant homology to the conserved J region of the DnaJ family of heat shock proteins. We earlier hypothesized that P58(IPK) was kept in an inactive state with its own inhibitor (termed I-P58(IPK)) in uninfected cells. We therefore attempted the purification and characterization of I-P58(IPK). The following data suggest that we have identified the molecular chaperone, hsp40, as I-P58(IPK). (i) The MonoP-purified I-P58(IPK) protein reacted with hsp40 antibody. (ii) This preparation demonstrated high specific activity in an in vitro functional assay containing only purified recombinant and native components. (iii) Purified, recombinant hsp40 protein inhibited P58(IPK) in an identical in vitro assay. (iv) Finally, we demonstrate that hsp40 directly complexes with P58(IPK), in vitro, suggesting the inhibition occurs through a direct interaction. Our data, taken together, provide evidence for a novel intersection between the heat shock and interferon pathways, and suggest that influenza virus regulates PKR activity through the recruitment of a cellular stress pathway.